Reevaluating the energy cost in locomotion: quadrupedal vs. bipedal walking in humans - Xu, Rui; Bao, Riqiang; Hu, Yixiang; Gao, Chong; Guo, Yuhan; Zhu, Yashu; Hu, Yuanyuan; Ning, Guang; Wang, Weiqing; Pan, Shijia (International Journal of Sports Medicine, 2025)
This study examines the energy expenditure and physiological responses associated with short-term quadrupedal locomotion compared to bipedal walking in humans. It aims to support evolutionary theory and explore quadrupedal locomotionʼs potential for enhancing fitness and health. In a randomized crossover design, 12 participants performed quadrupedal and bipedal walking on a treadmill at identical speeds. Physiological responses, including energy expenditure, carbohydrate oxidation rates, respiratory rate, and heart rate, were measured during both forms of locomotion. Quadrupedal walking significantly increased total energy expenditure by 4.15 Kcal/min [95% CI, 3.11 – 5.19 Kcal/min], due to a rise in carbohydrate oxidation of 1.70 g/min [95% CI, 1.02 – 2.24 g/min]. It also increased respiratory and heart rates, indicating higher metabolic demands. The exercise mainly activated upper limb muscles and the gluteus maximus in the lower limbs. Ten minutes of quadrupedal walking at the same speed as bipedal walking resulted in a 254.48% increase in energy consumption. This simple form of locomotion offers a strategy for enhancing physical activity, and supports the idea that energy optimization influenced the evolution of efficient bipedal locomotion.
Keywords: energy expenditure; evolution; quadrupedalism; exercise physiology